Karakteristik fisikokimia mi basah substitusi jenis ikan berbeda dengan penambahan egg white powder: Physicochemical characteristics of wet noodles substitution of different types of fish with the addition of egg white powder (EWP) - Amalia, Ayu Rizki; Sumartini, Sumartini; Azka, Aulia; Ratrinia, Putri Wening; Suryono, Muh; Saputra, Eko Novi; Hasibuan, Nirmala Efri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Noodles are a type of food that are liked by all groups and are often used as an alternative to rice substitutes. The protein nutritional content in noodle products is very low; therefore, it is necessary to add a high protein composition, one of which can come from various types of fish. A weakness of fish-based noodles is their physical characteristics, which are prone to breaking and lack chewiness, making them less favored by consumers. Therefore, it is necessary to use stabilizing agents such as Egg White Powder (EWP). This study aimed to determine the best fish flour for wet noodles, based on physicochemical characteristics and consumer preferences. The research method used was a completely randomized design (CRD) with different fish treatments: control, long-jawed mackerel (Rastrelliger sp.), Bombay-duck (Harpodonen nehereus), mackerel tuna (Euthynnus affinis), and Pangas catfish (Pangasius sp.). The tested parameters were sensory, proximate, and physical. Noodles with different types of fish contained water contents of 51.5-76.65%, protein 4.40-17.21, fat 0.20-6.53%, ash 1-2.82%, cooking loss 3.5-8.25%, rehydration capacity 35-65.24%, cooking time 75.75-115.28 seconds; elasticity 11.38-29.79%, and hardness value 881.40-4155.01 gf. The type of fish most favored as the main ingredient for wet noodles, based on the acceptance level of the panelists, was mackerel tuna. The use of fish as raw material can enhance the nutritional value of wet noodles.